1994
DOI: 10.1016/0378-1097(94)90594-0
|View full text |Cite
|
Sign up to set email alerts
|

A simple and reliable method of producing in vitro infections of cryptosporidium parvum (apicomplexa)

Abstract: A variety of techniques have been used to infect cell monolayers in culture with the protozoan, Cryptosporidium parvum. However, most of these methods rely on the use of trypsin and/or bile salts to excyst sporozoites in vitro, followed by washing sporozoites free of excystation solution prior to their addition to subconfluent monolayers. This method not only increases the amount of time required to establish infections in vitro, but also results in prolonged exposure of free sporozoites to environmental condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 13 publications
1
56
0
1
Order By: Relevance
“…drug therapies against the pathogen and for investigating hostparasite interactions (3,17). Due to the low infectivity of C. parvum to cultured cells, many attempts have been made to improve infectivity, including optimization of conditions for excystation (11,15,16,23,24), improvement of nutrients in culture medium (14,23), and other methods, such as centrifugation (26). In this investigation, we have demonstrated that the presence of NaTC or other bile salts, which are normally excreted in the gut during parasite infection, significantly enhanced the initial invasion of cultured cells by C. parvum and C. hominis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…drug therapies against the pathogen and for investigating hostparasite interactions (3,17). Due to the low infectivity of C. parvum to cultured cells, many attempts have been made to improve infectivity, including optimization of conditions for excystation (11,15,16,23,24), improvement of nutrients in culture medium (14,23), and other methods, such as centrifugation (26). In this investigation, we have demonstrated that the presence of NaTC or other bile salts, which are normally excreted in the gut during parasite infection, significantly enhanced the initial invasion of cultured cells by C. parvum and C. hominis.…”
Section: Discussionmentioning
confidence: 99%
“…To initiate in vitro infection, purified Cryptosporidium oocysts are often treated with sodium hypochlorite either alone or followed by sodium taurocholate (NaTC)-trypsin treatment before infecting cell monolayers. Several publications have dealt with assessment of the conditions and materials for optimal oocyst excystation and tissue culture infection by the excysted sporozoites (15,16,23,24). Upton et al (24) investigated the optimization of infection of oocysts treated with bleach without prior excystation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oocysts of different Cryptosporidium spp. were purified from feces by CsCl gradient centrifugation and surface sterilized with 10% Clorox as described previously (Upton et al, 1994). The number and purity of oocysts were determined by microscopic analysis.…”
Section: Microorganisms and Oocyst Purificationmentioning
confidence: 99%
“…For many years, the study of C. parvum and of effective drugs has been hampered by the lack of specific in vitro systems and a rapid method for evaluating the infection rate in a host cell population. However, in recent years, cell cultures for studying the life cycle and metabolic requirements of C. parvum have been developed (Arrowood et al, 1994;Griffiths et al, 1994;Upton et al, 1994a;Upton et al, 1994b;Upton et al, 1995), and it has been proposed that these cell cultures be used instead of animal models for pharmacological screening (Woods et al, 1995;Yang et al, 1996;Deng & Cliver, 1998).…”
Section: Introductionmentioning
confidence: 99%